1999
DOI: 10.1097/00002060-199911000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shoe Modifications on Center of Pressure and in-Shoe Plantar Pressures1

Abstract: This study was conducted to determine the effect of footwear modification on patients with neuromusculoskeletal disorders. Two analyses, the center of pressure and the in-shoe plantar pressures, were studied with the help of healthy volunteers so that the effect of shoe modifications could be assessed. The ground force under the sole of the shoe was measured while the subjects were walking, and the plantar pressure at the foot-insole interface and its distribution were measured while the subjects were in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 27 publications
3
17
0
1
Order By: Relevance
“…1, healthy subjects show a COP progression that starts from the heel, passes through the metatarsals, reaches the anterior and medial part of the foot, and ends on the hallux. This pattern is consistent with the COP pattern described by Hong et al (11) for healthy barefoot gait. Our data show that diabetic patients with severe neuropathy approach the floor with the most anterior part of the heel and perform their pushoff phase at the metatarsals level, as proven by the reduction of the COP progression along the longitudinal axis.…”
Section: Loading Timessupporting
confidence: 92%
“…1, healthy subjects show a COP progression that starts from the heel, passes through the metatarsals, reaches the anterior and medial part of the foot, and ends on the hallux. This pattern is consistent with the COP pattern described by Hong et al (11) for healthy barefoot gait. Our data show that diabetic patients with severe neuropathy approach the floor with the most anterior part of the heel and perform their pushoff phase at the metatarsals level, as proven by the reduction of the COP progression along the longitudinal axis.…”
Section: Loading Timessupporting
confidence: 92%
“…They are also broadly used as a screening tool for diabetic patients to establish the risk of ulceration 17,18) . Plantar pressure evaluation is also used to assess the effectiveness of footwear 19,20) and orthotic interventions 21,22) . Despite the growing use of plantar foot pressure assessments for research and clinical purposes, the factors that contribute to loading patterns of the foot remain poorly understood 23) .…”
Section: Introductionmentioning
confidence: 99%
“…Specific shoe design is based on pressure measurements from a floor-reaction imprint; our group has previously demonstrated the effectiveness of this design in relieving midfoot pressures without exacerbating hindfoot or forefoot pressures (Brown, et al, 2004). Other investigations of plantar pressure changes secondary to such modified footwear are widely reported in the literature (Chesnin, et al, 2000;van Schie, et al, 2000;Fuller, et al, 2001;VanZant, et al, 2001), but investigations of changes in joint motion (kinematics) and joint loading (kinetics) are less common (Peterson, et al, 1985;Schaff, et al, 1990;Mueller, et al, 1995;Dingwell, et al, 1999;Xu, et al, 1999). The studies that do exist are generally limited to observational or quantitative two-dimensional analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Significant changes were also seen in temporal parameters. Xu et al (Xu, et al, 1999) examined COP changes in shoes with medial and lateral support, and found a strong relationship between COP shifting and heel design. Mueller found an 11% reduction in step length with rocker sole use; Peterson (Peterson, et al, 1985) found minimal temporal changes in rocker shoe gait, although most differences occurred with increased walking speed.…”
Section: Introductionmentioning
confidence: 99%